THE EFFECT OF AGRICULTURAL LAND AREA AND AGRICULTURAL LABOR ON UNEMPLOYMENT IN INDONESIA - Saharuddin; Toha (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study analyzes the effect of agricultural land area and agricultural labor on the unemployment rate in Indonesia during the period 1994–2021 using multiple linear regression. The results show that agricultural land has a significant negative effect on unemployment, while agricultural labor has a significant positive effect. This indicates that expanding agricultural land can reduce unemployment, but an increase in agricultural labor without adequate land absorption may increase unemployment. The findings suggest the need for agricultural modernization and rural economic diversification to reduce unemployment more effectively.